Solvent Extraction of Polyphenolics from the Indigenous African Fruit Ximenia caffra and Characterization by LC-HRMS - Dewald Oosthuizen; Neill J. Goosen; Maria A. Stander; Aliyu D. Ibrahim; Mary-Magdalene Pedavoah; Grace O. Usman; Taiwo Aderinola (MDPI AG, 2018)
Indigenous and non-commercial fruits can be an important source of antioxidant polyphenols; however, the identity and content of polyphenols from non-commercial fruits are often poorly described. The study aimed to extract, identify, and quantify polyphenols from the skin of the indigenous Africa fruit Ximenia caffra, using solvent extraction. Three solvents (hexane, acetone, and 70% v/v ethanol) over three extraction times (30, 60 and 120 min) were used in a 32 full factorial experimental design to determine effects on polyphenol recovery, and individual polyphenolics were characterised using liquid chromatography high-resolution mass spectrometry (LC-HRMS). Ethanol was the most effective extraction solvent, and extracts had high levels of total phenolics and flavonoids (65 mg gallic and 40 mg catechin equivalents per gram dry sample respectively), and high antioxidant activity (18.2 mg mL−1 ascorbic acid equivalents). LC-HRMS positively identified 16 compounds, of which 14 were flavonoids including flavonoid glycosides, and indicated that concentrations of some flavonoids decreased for extraction times beyond 60 min. It was concluded that the fruit of Ximenia caffra is rich in natural polyphenolic antioxidants; the present work identified and quantified a number of these, while also establishing suitable solvent extraction conditions for the recovery of these potentially high-value compounds.